An Empirical Analysis of Financial Literacy As Mediator For Stock Investment Intention Among University Students - Sembel, Jacquelinda Sandra; Widjaja, Anton Wachidin; Antonio, Ferdi (International Journal of Business Studies, 2024)
The participation of generations Y (millennials) and Z in the stock market is the lowest in terms of capital invested. There is an urgency to involve the young generation in stock investment. Therefore, the aim of this study is to analyze the influencing factors of stock investment intention in university students. Four variables were included: financial literacy, risk tolerance, internal locus of control, and the stock investment intention of university students. The study also examines the mediating role of financial literacy. This quantitative study involved 153 students from a private university in Tangerang, using purposive sampling. Data collection was done using a survey questionnaire, distributed online. Partial Least Square Structural Equation Modeling (PLS-SEM) was used for data analysis. The study discovered internal locus of control is not found to positively influence stock investment intention, but financial literacy and risk tolerance, respectively, have a positive influence on stock investment intention. The study also demonstrated that Internal Locus of Control and Risk Tolerance have a substantial impact on Financial Literacy. Finally, this study confirmed the mediating function of financial literacy in the interaction between Risk tolerance and Stock Investment Intention, as well as between Internal Locus of Control and Stock Investment Intention. Keywords: Stock Investment Intentions, Internal Locus of Control, Risk Tolerance, Financial Literacy, mediation